Aortic properties and atrial electrophysiology in the young and old football players - Hasdemir,Hakan (2011)
OBJECTIVE: The purpose of this study was to investigate the differences between P wave dispersion, aortic elastic properties and transthoracic echocardiographic findings in the young and old football players compared to control groups in order to asses the influence of regular sportive activity on aortic distensibility and its potential effect on atrial electrophysiology. METHODS : We recruited 42 young football players with a training history of many years. The control group was formed by 27 healthy sedentary men. Twenty-three healthy retired football players of a professional football club aged over 50 years were included in the study as old group and 18 subjects over 50 year old who did not perform regular exercise when they were young were included in the control group of old subjects. RESULTS: The heart rate and ejection fraction were decreased in the young football players. There were no significant differences in the aortic elastic parameters and P wave dispersion between young football players and control group. But in old subjects with sustained participation in regular sportive activity, the significant difference of left ventricular dimension, wall thickness and systolic functions detected in the young group disappeared while increase in the left atrial diameter became significant. CONCLUSION: Potential effect of aortic elastic properties which changes with age, on atrial electrophysiology through increasing P wave dispersion was shown.